PECULIARITIES OF MEDICAL-PSYCHOLOGICAL REHABILITATION OF PATIENTS WITH CERVICAL OSTEOCHONDROSIS (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
In this article we have considered patients’ physiological, psychological and social peculiarities with cervical osteochondrosis, as well as the ways of its prevention and treatment. It has been detected that patients with cervical osteochondrosis have reduction of activeness of defense mechanisms, which manifests in arterial pressure as well as anxiety, aggression and low level of activity. At the same time these patients are described by high level of tiredness. The complex program, based on the obtained data (includes physical, physiotherapeutic and psychological affective technologies), promotes neurovegetative system optimization, and as a result affects the improvement of patients life quality.
Keywords: cervical osteochondrosis, defense mechanisms, state of health